Analisis Kebutuhan Media Pembelajaran Video Drama Pada Kelas XI/F SMAN 7 Padang - Soleh Pangidoan Siregar; Ridho Bayu Yefterson (Jurusan Sejarah FIS UNP, 2022)
This research is part of the research on the development of drama video learning media to train students' chronological thinking skills. This study aims to explain the results of the analysis stage of why video drama media is needed by educators and students in the history learning process at SMAN 7 Padang. This study uses a descriptive qualitative method by using interview and observation techniques to collect and obtain data. The results of this study are in the form of a description of the stage of analyzing the needs of media for learning drama video at XI/F at SMAN 7 Padang on the Padri War material.